A prospective, observational, multicentre study comparing tenecteplase facilitated PCI versus primary PCI in Indian patients with STEMI (STEPP—AMI). Issue 1 (20th August 2014) - Victor, Suma M; Subban, Vijayakumar; Alexander, Thomas; G, Bahuleyan C; Srinivas, Arun; S, Selvamani; Mullasari, Ajit S
Abstract : Objective: To compare the efficacy of pharmacoinvasive strategy versus primary percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI). Primary PCI is the preferred treatment for STEMI, but it is not a feasible option for many. A pharmacoinvasive strategy might be a practical solution in the Indian context, although few empirical data exist to guide this approach. Methods: This is a prospective, observational, multicentre pilot study. Two hundred consecutive patients with STEMI aged 18–75 years, presenting within 12 h of onset of symptoms and requiring a reperfusion strategy, were studied from five primary PCI capable centres in South India. Patients who opted for pharmacoinvasive strategy (n=45) formed group A. Group B consisted of patients treated with primary PCI (n=155). One patient was lost to follow-up at 1 year. The primary end point was a composite of death, cardiogenic shock, reinfarction, repeat revascularisation of a culprit artery and congestive heart failure at 30 days. Results: The primary end point occurred in 11.1% in group A and in 3.9% in group B, p=0.07 (RR=2.87; 95% CI 0.92 to 8.97). The infarct-related artery patency at angiogram was 82.2% in group A and 22.6% in group B (p<0.001). PCI was performed in 73.3% in group A versus 100% in group B (p<0.001), and a thrombus was present in 26.7% in group A versus 63.2% in group B (p<0.001). Failed fibrinolysis occurred in 12.1% in group A. There was no difference in bleeding risk, 2.2% in group A versus 0.6% in group B, (p=0.4). Conclusions: This pilot study shows that a pharmacoinvasive strategy can be implemented in patients not selected for primary PCI in India and hints at the possibility of similar outcomes. Larger studies are required to confirm these findings. Trial registration number: Trial is registered with Clinical trial registry of India, CTRI number: REF/2011/07/002556.